MOTIVATIONAL ANALYSIS OF THE NAMES OF SPIRITS-“MASTERS” OF LOCI: based on material from Russian dialects of the Perm Region (Philological Studies, 2020)
The article is devoted to the study of nominations of the “master” spirits of the loci (boggart of the bathhouse, boggart of the house, wood goblin) that function in the Russian dialects of the Perm region. The purpose of the work is to determine the motivational base for these units, which involves, firstly, identifying semantic donor spheres, units of which serve as the basis for the emergence of these nominations, and secondly, building motivational models for the formation of such names. Such analysis makes it possible to detect signs of characters that are verbalized in their notation. To solve these problems, we use the method of ethnolinguistic interpretation of semantic fields proposed by E.L. Berezovich. The analysis made it possible to establish that the main motivational basis for the names of the “master” spirits of loci in Perm dialects are units of the semantic sphere “Man”; then, in terms of importance, the motivational spheres “Locus” and “Demons” follow, from the units of which a large number of nominations of these characters are also formed; the least important for the formation of the units under consideration are the spheres “Animal” and “Оbject”, as well as “Atmospheric phenomena”. The Perm motivations of the “master” spirits are based on the following motivational signs: the locus of the spirit; the demonic nature of the characters; transformation; the need to respect and appease the spirits of space.
Keywords: folk demonology; boggart of the bathhouse; boggart of the house; wood goblin; demonological lexis; Russian dialects; Perm Region